External sustainability analysis: cyclical versus non-cyclical current account balances in the Eurozone - Tinti, Tamara (2016)
The persistent widening phase of current account balances1 recorded in the last years has sharply reversed during the crisis of 2008. In order to predict their future evolution, it is fairly necessary to identify both structural and cyclical factors and understand in which way they could affect the imbalances. The purpose of this paper is to determine the existing link between these components using a panel of 28 European countries from 1972 and 2014. We found that a major contribution on those balances is provided in large part by structural factors.